Phylogeny of the jacchus group of Callithrix marmosets based on complete mitochondrial genomes. Issue 1 (20th October 2016) - Malukiewicz, Joanna; Hepp, Crystal M.; Guschanski, Katerina; Stone, Anne C.
Abstract: Objectives: Two subgroups make up the marmoset genus Callithrix . The " aurita " group is composed of two species, whereas evolutionary relationships among the four species of the " jacchus" group remain unclear. To uncover these relationships, we first sequenced mitochondrial genomes for C. kuhlii and C. penicillata to complement data available for congeners. We then constructed a phylogenetic tree based on mtDNA heavy chain protein coding genes from several primates to untangle species relationships and estimate divergence times of the jacchus group. Materials and Methods: MtDNA genomes of C. kuhlii and C. penicillata were Sanger sequenced. These Callithrix mitogenomes were combined with other publically available primate mtDNA genomes. Phylogenies were produced using maximum likelihood and Bayesian inference. Finally, divergence times within the jacchus group of marmosets were estimated with Bayesian inference. Results: In our phylogenetic tree, C. geoffroyi was the sister to all other jacchus group species, followed by C. kuhlii, while C. jacchus and C. penicillata diverged most recently. Bayesian inference showed that C. jacchus and C. penicillata diverged approximately 0.70 MYA and that the jacchus group radiated approximately 1.30 MYA. Discussion: Callithrix nuclear and mtDNA phylogenies frequently result in polytomies and paraphyly. Here, we present a well‐supported phylogenetic tree based on mitochondrial genome sequences, which facilitates the understanding of the divergence of the jacchus marmosets. Our results demonstrate how mitochondrial genomes can enrich Callithrix phylogenetic studies by alleviating some of the difficulties faced by previous mtDNA studies and allow formulation of hypotheses to test further under larger genomic‐scale analyses.